Alteration in tRNA Methyltransferase Activity in Mengovirus Infection: Host Range Specificity - Wilkinson, Ray (1973)
The tRNA methyltransferase activity in mengovirus-infected L cells, HeLa cells, and Maden Derby bovine kidney cells has been examined during the course of infection. The first two cell lines yield a productive infection, but have different kinetics of inhibition of host RNA synthesis, whereas the bovine kidney cells are a restrictive host. In infected L cells the enzymes show altered capacity and base specificity throughout the infection. In infected HeLa cells and in infected bovine kidney cells less marked changes were seen. No inhibitors or activators of the enzymes were detected in any of the infected cell lines. Labeling experiments in infected cells indicated that in infected L cells synthesis of RNA was inhibited to a greater degree than was methylation of RNA. The consequence of this would be a hypermethylation of RNA. The methylated derivatives synthesized in infected L cells showed changes in relative proportions. Infection of HeLa cells and bovine kidney cells did not show such marked effects on methylation of RNA.